2000
DOI: 10.1063/1.1323996
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic tuning behavior in epitaxial Ba0.5Sr0.5TiO3 thin films

Abstract: The tuning properties of epitaxial Ba0.5Sr0.5TiO3 (BST) thin films were investigated by a scanning microwave microscope (SMM) and an LCR meter. Although the BST films on LaAlO3 and MgO substrates showed similar tuning behavior when measured by the LCR meter at 1 MHz, remarkably different tuning properties were observed in the planar capacitors measured by SMM. The BST films on LaAlO3 substrates were hardly tuned when measured by SMM, while the BST films on MgO showed significant tuning behavior between the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…The strain in the epitaxial films also affects their local tuning properties. By using a scanning microwave microscope (SMM) method, Hyun et al 53 investigated the effects of different strains on the local tuning properties of epitaxial (Ba 0.5 Sr 0.5 )TiO 3 thin films grown on MgO (001) and LAO (001) substrates. It is interesting to observe remarkably different tuning properties in the planar capacitors measured by SMM.…”
Section: Film Stressmentioning
confidence: 99%
“…The strain in the epitaxial films also affects their local tuning properties. By using a scanning microwave microscope (SMM) method, Hyun et al 53 investigated the effects of different strains on the local tuning properties of epitaxial (Ba 0.5 Sr 0.5 )TiO 3 thin films grown on MgO (001) and LAO (001) substrates. It is interesting to observe remarkably different tuning properties in the planar capacitors measured by SMM.…”
Section: Film Stressmentioning
confidence: 99%
“…In this work, we investigate the dielectric properties over a very wide range of microwave frequencies ͑45 MHz-50 GHz͒, rather than at the lower, narrower frequency ranges ͑Ͻ10 GHz͒ more commonly studied. [3][4][5] The material investigated is Ba 0.5 Sr 0.5 TiO 3 , which has a Curie temperature ͑T c ͒ around room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The small tunability can be interpreted as a result of inplane compressive stress of BaTiO 3 film exhibiting large dielectric anisotropy. Hyun et al [9] reported that the in-plane compressive stress in the BST film with an interdigital electrode decrease the ionic displacement along the electric field parallel to substrate and large tunability should exist near the electrode where the electric field is normal to the substrate since the BST film has distorted tetragonal structure with c/a of 1.009 by in-plane compressive stress. In this work, the measured c/a ratio of epitaxial BaTiO 3 film was 1.04.…”
Section: Resultsmentioning
confidence: 98%